On maximal parallel application of rules in rewriting P systems - Zandron, Claudio (Journal of membrane computing, 2023)
In rewriting P systems, that is P systems using structured strings instead of atomic symbols, rules can be applied in parallel on all strings, but a single rule at a time can be applied on each string. Nonetheless, parallel application of rules also on each string has been considered in various works. This leads to possible application of rules with conflicting target indications on the same string, and different strategies have been considered to face this problem; relations among different classes of languages generated in this way have been investigated in the literature. We continue the investigation on this subject, by highlighting some relations among different classes of maximally parallel rewriting P systems by means of direct simulations. The advantages of such simulations are highlighted, by showing how theoretical results concerning one such type of systems can immediately be adapted to the corresponding simulating systems.